Mussel-inspired thermo-switchable underwater adhesive based on a Janus hydrogel - Hiroya Abe; Daichi Yoshihara; Soichiro Tottori; Matsuhiko Nishizawa (NPG Asia Materials)
Abstract On-demand underwater adhesives with excellent adhesive and gentle detachment properties enable stable connections to various biomedical devices and biointerfaces and avoid the risk of harmful tissue damage upon detachment. Herein, we present a Janus hydrogel adhesive that can reversibly switch its adhesion strength, which is controlled by temperature, using a thermoresponsive polymer and mussel-inspired molecules. This thermoswitchable adhesive (TSA) hydrogel displays both strong adhesion and gentle detachment with an over 1000-fold gap in underwater adhesion strength onto glass, titanium, aluminum, and Teflon substrates when exposed to temperatures above and below the lower critical solution temperature (LCST). The adhesion switch is possibly caused by the change in toughness of the TSA hydrogels with temperature because the Janus hydrogel possesses gradient crosslinked structures. Moreover, the lowermost surface is sufficiently soft to gently detach from the substrate below the LCST. The electrode-integrated hydrogel remains on human skin, and electrical signals are continuous over 10 min above the LCST. In contrast, commercially available hydrogel electrodes quickly swell and detach from the skin. The thermoswitchability of the TSA hydrogel, with its robust adhesion and gentle detachment, offers significant potential for biomedical applications characterized by minimally invasive procedures.